Peningkatan Hasil Belajar Dan Kemampuan Berpikir Kritis Peserta Didik Dalam Mata Pelajaran Pendidikan Agama Katolik Melalui Model Pembelajaran Problem Based Learning di Kelas VIII UPTD Smp Negeri 4 Moro’o - Saverius Sozanolo Waruwu; Brigida Intan Printina (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Saverius Sozanolo Waruwu, 2024. This study aims to improve students' critical thinking skills and learning outcomes in the Catholic Religious Education subject for eighth-grade students at UPTD SMP Negeri 4 Moro’o. Based on initial observations, it was found that students' learning outcomes had not met the Minimum Mastery Criteria (KKTP), ranging between 60-75, and their critical reasoning skills were still at a sufficient level. This was due to the teaching methods being primarily lecture-based and narrative. To address this issue, the researcher attempted to implement the Problem Based Learning (PBL) model in Catholic Religious Education classes. The subjects of this study consisted of five eighth-grade students. In the first cycle, 80% of the students achieved mastery, but this did not meet the target of 85%. After improvements were made in the second cycle, learning outcomes increased to 100%, with all students reaching the set mastery level. Additionally, the students' critical thinking skills also improved. In the first cycle, the average critical thinking score was 2.9, which was categorized as sufficient. However, in the second cycle, after the implementation of PBL, the score increased to 3.65, indicating a significant improvement in critical thinking skills. Based on the research findings, it can be concluded that the implementation of the Problem Based Learning model is effective in enhancing students' critical thinking skills and learning outcomes.